USE OF THE "WORKING WITH OBJECTS" METHODOLOGY IN PREPARING FOR INTERNATIONAL STUDIES - Mirkhalilova Nargiza Akbarovna (American Journals Publishing, 2023)
This article describes the guidelines for using the "Working with objects" methodology for mathematics and natural sciences in preparation for TIMSS international studies, and the ability to adapt to social life through the methodology.
Keywords: TIMSS research, STEM, natural sciences, functional literacy,